Clinical marine biomedicine: An emerging area in clinical and translational medicine - Xiaojun Yan; Wanxin Duan; Xiangdong Wang (Clinical and Translational Discovery)
Abstract Marine biomedicine is an important field in oceanology and bio‐ecosystem and has evolved significantly alongside advances in biotechnology and growing understanding of marine life. In this perspective, we propose a refined concept of clinical marine biomedicine, with a clear mission to establish an emerging discipline that bridges marine biomedicine and clinical practice. The exploration of marine‐origin sources should be emphasised, with a strong focus on the identification, validation and development of human disease‐specific diagnostics and target‐oriented pharmaceutics. The perspective headlines some of critical components, including marine‐oriented human evolution and development, humanised marine‐based models, biomarker innovation and validation, marine microbiomes and metabolites, and target nutrition and therapy. We envision that clinical marine biomedicine will become a crucial pillar clinical molecular medicine, contributing to the improvement of human health and the prognosis of patient.